SURVEYING - A DUAL REGULATED PROFESSION WITH TRIPLE MEMBERSHIP - Ivanov, Ivan (E-Journal VFU, 2025)
The surveying profession has been repeatedly regulated and placed under the supervision of various scientific organizations, chambers, unions and other types of societies. Gradually, over the years, geodesy develops its potential as, in addition to solving its own problems of determining the shape of the Earth, dimensions, gravitational field, etc., it is increasingly skilfully applied and contributes to the solution of diverse activities and problems in other sciences and fields. This places more and more complex requirements on the future engineer-surveyors, while at the same time specific regulations are imposed regarding the individual types of activities that surveyors perform.
Keywords: Surveying; legal capacity; regulated profession; engineer; designer